Aggregate and heterogeneous sectoral growth effects of foreign direct investment in Egypt. Issue 4 (2nd August 2020) - Ingham, Hilary; Read, Robert; Elkomy, Shimaa
Abstract: This paper investigates the sectoral impacts of foreign direct investment (FDI) on growth in Egypt between 1990 and 2007 based on a unique data set. It highlights the aggregation bias inherent in many empirical studies that focus solely on the economy‐wide effects of foreign investment. Aggregate inflows of FDI are shown to be detrimental to the country's economic growth performance, possibly as a result of the "crowding‐out" of more productive domestic investment. Some positive sector‐specific effects, however, are found for investment in manufacturing and petroleum, which also has beneficial spillovers into other sectors. FDI in the finance and retail and telecommunications and information technology sectors are found to generate significantly negative growth effects, while those in services and tourism are negative but generally insignificant. These findings suggest that "market‐seeking" FDI in certain sectors has conspicuous "crowding‐out" effects, possibly owing to insufficient domestic absorptive capacity. The results of this study further demonstrate the importance of potential sectoral heterogeneity of own sector and inter‐sectoral economic growth effects of FDI. It therefore highlights the critical need for policymakers to take a more disaggregated sectoral‐level evaluation of the benefits of foreign investment, particularly in developing economies such as Egypt.